EFFECT OF CARICA PAPAYA L LEAF ON MENSTRUAL PAIN AND PROSTAGLANDIN LEVEL IN ADOLESCENT WITH PRIMARY DYSMENORRHEA: A TRUE EXPERIMENT - Siska Nurul Abidah; Soeharyo Hadisaputro; Runjati Runjati; Syarief Thaufik Hidayat; Ari Suwondo; Donny Kristanto Mulyantoro (Belitung Nursing Journal, 2017)
Background: Primary dysmenorrhea occurs because of the excessive amount of prostaglandins in the blood. Papaya leaf extract is considered to be able to reduce prostaglandin and menstrual pain. Objective: This study aims to prove that papaya leaf extract (Carica Papaya L.) can decrease the level of menstrual pain and prostaglandin levels in primary dysmenorrhea. Methods: A true experimental study with randomized pretest posttest control group design. There were 32 samples recruited using simple random sampling, with 16 each assigned to an experiment group and a control group. Numerical Rating Scale (NRS) was used to measure menstrual pain, and the level of prostaglandin was measured using the enzyme-linked immunosorbent assay (ELISA) method. Independent t-test and paired t-test were performed for data analysis. Results: There was statistically significant difference of menstrual pain and prostaglandin level before and after intervention with p-value 0.000 (<0.005), which indicated that papaya leaf extract had a significant effect on reducing menstrual pain. The decrease of menstrual pain in the experimental group was -3.375 and in the control group was -3.438; while the decrease of prostaglandin level in the experimental group was -56.971 and in the control group was -57.557. Conclusion: Provision of papaya leaf extract (Carica Papaya L.) significantly decreased the level of menstrual pain and prostaglandin levels in primary dysmenorrhea. Papaya leaf extract can be used as a safe and effective herbal medicine for primary dysmenorrhea which has almost the same efficacy as mefenamic acid.